A system using patient‐specific 3D‐printed molds to spatially align in vivo MRI with ex vivo MRI and whole‐mount histopathology for prostate cancer research. Issue 1 (2nd August 2018) - Wu, Holden H.; Priester, Alan; Khoshnoodi, Pooria; Zhang, Zhaohuan; Shakeri, Sepideh; Afshari Mirak, Sohrab; Asvadi, Nazanin H.; Ahuja, Preeti; Sung, Kyunghyun; Natarajan, Shyam; Sisk, Anthony; Reiter, Robert; et al.
Abstract : Background: Patient‐specific 3D‐printed molds and ex vivo MRI of the resected prostate have been two important strategies to align MRI with whole‐mount histopathology (WMHP) for prostate cancer (PCa) research, but the combination of these two strategies has not been systematically evaluated. Purpose: To develop and evaluate a system that combines patient‐specific 3D‐printed molds with ex vivo MRI (ExV) to spatially align in vivo MRI (InV), ExV, and WMHP in PCa patients. Study Type: Prospective cohort study. Population: Seventeen PCa patients who underwent 3T MRI and robotic‐assisted laparoscopic radical prostatectomy (RALP). Field Strength/Sequences: T2 ‐weighted turbo spin‐echo sequences at 3T. Assessment: Immediately after RALP, the fresh whole prostate specimens were imaged in patient‐specific 3D‐printed molds by 3T MRI and then sectioned to create WMHP slides. The time required for ExV was measured to assess impact on workflow. InV, ExV, and WMHP images were registered. Spatial alignment was evaluated using: slide offset (mm) between ExV slice locations and WMHP slides; overlap of the 3D prostate contour on InV versus ExV using Dice's coefficient (0 to 1); and 2D target registration error (TRE, mm) between corresponding landmarks on InV, ExV, and WMHP. Data are reported as mean ± standard deviation (SD). Statistical Testing: Differences in 2D TRE before versus after registration were compared using the Wilcoxon signed‐rank test ( P < 0.05 considered significant). Results: ExV (duration 115 ± 15 min) was successfully incorporated into the workflow for all cases. Absolute slide offset was 1.58 ± 1.57 mm. Dice's coefficient was 0.865 ± 0.035. 2D TRE was significantly reduced after registration ( P < 0.01) with mean (±SD of per patient means) of 1.9 ± 0.6 mm for InV versus ExV, 1.4 ± 0.5 mm for WMHP versus ExV, and 2.0 ± 0.5 mm for WMHP versus InV. Data Conclusion: The proposed system combines patient‐specific 3D‐printed molds with ExV to achieve spatial alignment between InV, ExV, and WMHP with mean 2D TRE of 1–2 mm. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:270–279.